(untitled) (Journal of Pure & Applied Sciences, 2023)
The TEP, or Seebeck coefficient (S), for five bulk glasses in different compositions of binary semiconducting CoO–TeO2 glasses has been measured in the temperature range 304–490K. The glasses were prepared by melting dry mixtures of analytical reagent grads of CoO and TeO2 at a temperature of 1000 °C for 1h using quenching form the melt technique. TEP measurements have been performed utilizing specifically designed sample holders on annealed samples. The glasses were found to be n–type semiconductors with S in the range from –293 to –460 μV/K. S was found to be independent of temperature for all glass compositions, and Heikes’ formula adequately satisfied the TEP experimental results. The analyses provide evidence on the polaron formation and the disorder energy due to random fields.